Optimisation Of Ud Barokah Furniture Business Operations In Kalirejo Village, Sumbermalang District, Situbondo Regency - Muhammad Muhjibul Ikhsan; Misbahul Munir; Siti Masroratin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Every company, be it industrial, trade or service companies, has the same goal, namely to obtain maximum profits. To achieve this goal, companies need to optimize their production results, because with optimal production results they will also obtain maximum profits. The UD Al Barokah Furniture Company processes or produces cupboards, couches, chairs, toilets, etc. By using several stages of the production process, such as felling wood, transporting wood, cutting wood, sawing, and refining wood to produce better and better wood. The research method used is a qualitative approach. Determining the data source uses a purposive sampling technique, while the data collection method uses observation, interviews and documentation methods. The data analysis method uses reduction, presentation and drawing conclusions. The data validity method uses source triangulation. The conclusions of this research are: (1) The way to optimize UD Al Barokah Furniture Business Operations is to increase capital by setting aside a small amount of profits obtained, without borrowing business capital from banks or other financial institutions. (2) Not being able to buy a generator when the electricity goes out, the process of making cupboards, cots, chairs, toilets and so on is not optimal, because some machines still use electricity. (3) When drying in the rainy season for drying wood using a shady place, when the electricity goes out, the process of making cupboards, couches, chairs, toilets and so on uses manual tools, and other supporting factors use raw materials mixed with teak wood and wood. milina